Classmotvr: Web application to encourage student’s participation in class using gamification / Mariatulqibtiah Makhtar - Makhtar, Mariatulqibtiah (2017)
“ClassMotvr” is a system designed to motivate students to participate more in class rather than being passive students. In addition, it is also built to decrease tardiness of the students. Tardiness can be related with student’s participation as it might be the reason why an active engagement during learning cannot be obtained. The first objective of this system is to design a system that can encourage student participation using gamification. Next is to develop the designed system. Lastly is to test the functionalities of the developed system. The technique that has been applied to the system is gamification technique. It has been applied for points, rewards, leaderboard, and status. Furthermore,gamification is used because it can persuade people to behave according to the individual desires by using game-design elements. Analysis of some similar system using gamification technique also has been done in order to understand about the project. The methodology used for this project is Rapid Application Development (RAD). Functionality test has been conducted. This is to ensure that the functionalities of each test case can be executed without any error. Overall, there are few enhancements that could be proposed for this project in the future such as broadens the scope of the system towards all Universiti Teknologi MARA instead of UiTM (Melaka) Kampus Jasin only. Other than that, this system also can be enhancing by adding more features such as badges, and etc. Furthermore, there are more rooms for improvement on this project.